METHODOLOGICAL PRINCIPLES OF STUDY STUDY FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS - Havrylyuk, O.O. (Pedagogy of Higher and Secondary Education, 2002)
In clause the advantages and lacks of various methods of testing of a state of communicative culture of the future teachers are opened.